RETRACTED: Priority factors of the nutritional model that influence the prenatal development of the fetus - Abdullayeva Zamira Sh.; Shikhnazarova Guzal A. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001